Investigation of Visceral Leishmaniasis among 192 Dog Carcasses Killed by Road Accidents in Khorasan Razavi, North-eastern Iran during 2014-2016 - Elham MOGHADDAS; Abdolmajid FATA; Mehdi ZAREAN; Majid DERAKHSHANI; Mahdi FAKHAR; Seyed Aliakbar SHAMSIAN (Tehran University of Medical Sciences, 2018)
Background: Visceral leishmaniasis (VL), so-called Kala-azar is a life threating parasitic infectious disease caused by Leishmania spp. L. infantum is the main causative agent for Mediterranean form of Kala-azar which is endemic in northeastern Iran. This study attempted to investigate existence of canine visceral leishmaniasis (CVL) in Khorasan Razavi. Methods: Between 2014 and 2016, tissue samples collected from spleen and liver of 192 stray dogs were examined to investigate existence of L. infantum. Kinetoplast DNA (k-DNA) PCR was performed to identify the species of parasites. The positive PCR products were sequenced in both directions to confirm the kDNA PCR results Results: Among samples obtained from 192 dogs, kinetoplast DNA of L. infantum was detected in two female dogs. L. infantum was confirmed by sequence analysis of PCR products. Conclusion: Our data confirm stray dogs play as potential reservoirs for VL in this province. Further investigation will be necessary to clear role of stray dogs in the transmission of L. infantum to human and domestic dogs.